Sosialisasi Pengaruh Stres Oksidatif Terhadap Penderita Obesitas Usia Remaja di Desa Balangtanaya Kab. Takalar - Wahyu Munandar; Aminuddin (ABDI SAMULANG: Jurnal Pengabdian Kepada Masyarakat, 2023)
Socialization about the Effect of Oxidative Stress on Obese People in Adolescent Age in Balangtanaya Village, North Polongbabgkeng, Takalar Regency is one of the Tridharma of Higher Education, namely community service. This activity aims to educate the people of Balangtanaya Village about how to exercise according to their needs, namely with intensity that considers age, gender and physical activity. Especially teenagers who tend to do excessive physical activity. This is what can result in oxidative stress. Exercise regularly by paying attention to the Body Mass Index (BMI) in order to control body weight to remain in the normal category. The solution offered to the community is expected to provide benefits so that the residents of Balangtanaya Village understand the portion of each physical activity carried out. Exercising with moderate intensity but long duration can be a solution in preventing the production of Reactive Oxygen Species (ROS) or known as free radicals in the body. Exercising regularly and consuming foods or fruits that contain antioxidants are the solutions offered at this activity.